ANALISIS KESULITAN BELAJAR PESERTA DIDIK PADA MATERI SISTEM PEREDARAN DARAH SELAMA PROSES PEMBELAJARAN JARAK JAUH (PJJ) DI SMA N 1 BANDAR SEI KIJANG - Tri Mailinda Yuspita Sari; Yuslim Fauziah; Darmawati Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Distance Learning (PJJ) is a form of learning that can be used as a solution during the COVID-19 pandemic. In the distance learning process (PJJ) students have learning difficulties. Therefore, this study aims to analyze students' learning difficulties and the factors that cause students' learning difficulties, one of which is the material of the circulatory system. This type of research is descriptive quantitative research using written test questions and questionnaires conducted at SMA N 1 Bandar Sei Kijang. The object of this research is the students of class XII MIPA, totaling 50 students. The results of this study indicate that the learning difficulties of class XII students of SMA N 1 Bandar Sei Kijang on the material of the circulatory system during the Distance Learning (PJJ) process in general are still quite difficult with an average percentage of 52,2% the criteria are quite difficult. While the factors that cause learning difficulties in general, the average percentage is 73,0%, the criteria are quite difficult. However, the factors that cause learning difficulties for students are more dominant in the family environment, namely 77,2% of difficult criteria and in the school environment of 82,5% of difficult criteria. This shows that the students of class XII MIPA SMA N 1 Bandar Sei Kijang on the material of the circulatory system during the Distance Learning process (PJJ) still have many difficulties in learning..Key Words: Circulatory System, Learning Difficulties, Distance Learning (PJJ)